Unmasking Mei: A Lacanian psychoanalytic study of identity formation in Turning Red movie - Ersa Dewanti; Rusfandi Rusfandi; Nara Sari (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2025)
This study applies Jacques Lacan’s psychoanalysis theory toanalyze the identity formation of Mei, the main character in themovie Turning Red. Using a qualitative method with contentanalysis, it explores Mei's identity development throughout thefilm. The results show that Lacan’s theories of the Imaginary,the Symbolic, and the Real significantly shape the maincharacter's identity. Mei’s transformation into a red panda iscrucial in this process. The Imaginary aspect drives her toembody the ideal princess, highlighting the influence ofparental expectations and social norms on her self-image. TheSymbolic dimension reveals her internal conflicts and pressuresfrom family rules related to cultural traditions, while the Realreflects her rejection of the tradition of sealing the red panda.This analysis demonstrates that Mei’s identity is shaped bysocietal pressures, social norms, and family traditions. Thestudy contributes to the discourse on animated films andpsychoanalysis by showing how teenage girls navigate internalpsychological conflicts influenced by idealized images.Ultimately, it emphasizes the exploration of identity formationwithin a cultural context, showcasing psychoanalysis as a toolfor understanding individual identity development.